Effects of decontaminated fish oil or a fish and vegetable oil blend on persistent organic pollutant and fatty acid compositions in diet and flesh of Atlantic salmon (Salmo salar) - Sprague, Matthew; Bendiksen, Eldar Asgard; Dick, James R; Strachan, Fiona; Pratoomyot, Jarunan; Berntssen, Marc H G; Tocher, Douglas R; Bell, J Gordon (British Journal of Nutrition, 2010)
The health benefits of seafood are well documented and based on the unique supply of n-3 highly unsaturated fatty acids (HUFA). Aquaculture now contributes ~50% of food-grade seafood globally and Atlantic salmon is a rich source of n-3 HUFA. However, salmon and other oily fish can accumulate lipophilic persistent organic pollutants (POPs), including dioxins (PCDD/Fs), polychlorinated biphenyls (PCBs) and polybrominated diphenyl ethers (PBDEs), derived largely from feed. In this study, triplicate groups of salmon, of initial weight 0.78 kg were fed one of three experimental diets for 11 weeks. The diets were coated with either a northern fish oil (FO) with a high POPs content (cNFO), the same oil that had been decontaminated (deNFO) or a blend of southern fish oil, rapeseed and soybean oils (SFO/RO/SO). Dietary PCDD/F + dioxin-like PCB (DL-PCB) concentrations were 17.36, 0.45 and 0.53 ng TEQ/kg, respectively. After 11 weeks, the flesh concentrations in fish fed the cNFO, deNFO and SFO/RO/SO diets were 6.42, 0.34 and 0.41 ng TEQ/kg, respectively. There were no differences in flesh eicosapentaenoic (EPA) and docosahexaenoic acids (DHA) between fish fed the cNFO or deNFO diets although EPA and DHA were reduced by 50 and 30%, respectively, in fish fed the SFO/RO/SO diet. Thus, decontaminated FO can be used to produce salmon high in n-3 HUFA and low in POPs. Salmon produced using deNFO would be of high nutritional value and very low in POPs and would utilise valuable fish oils that would otherwise be destroyed due to their high pollutant concentrations.